Proposta de um jardim sensorial para educação ambiental e promoção da saúde no ensino médio - Lopes, Iarima Naama Ferreira (2021)
The teaching and learning processes should generate great stimulus and performance to students and every day this process is being renewed from the use of new theories, methodologies and resources in the classroom. For Biology Teaching, focusing on the Botany content, for example, teachers seek to use non-formal spaces and other practical activities to avoid a fragmentation between theory and the reality of their students. However, a distancing between human beings and nature is increasingly evident, and an intervention that contributes to a rapprochement that brings mutual benefits is necessary. In this perspective, this dissertation aimed to develop a teaching guide for the construction and use of a Sensory Garden as an alternative to Environmental Education (EE), based on Meaningful Learning and Project-Based Learning. During the discussion, we address issues related to the basic concepts of environmental education, as well as the historical path that has been traced for Environmental Education to be inserted and discussed in education. The development of the research occurred in two distinct stages, the first step consisted of the application of a diagnostic questionnaire conducted online through the Google Forms platform with students from the 1st year of high school at the Federal Institute of Amazonas (IFAM), and the second step consisted of evaluating the proposal inserted into the educational product through the Delphi method, with application of questionnaires and sending feedback from previous rounds online. The Delphi rounds were directed to a group of reviewers from different educational institutions, in addition to undergraduate students in Biological Sciences. For the analysis of the results in both stages, a qualitative analysis was adopted. In general, the results obtained in the first stage provided us with important indications that the students of Basic Education present in their cognitive structure, basic concepts of EE observed through the discursive answers of the diagnostic survey, and that, as mentioned by them, there is a preference in practical activities when working on issues related to the theme. Regarding the Delphi method, the results reinforced the need to approach Environmental Education through methodologies that involve and make the student the protagonist of his own knowledge, in addition to the importance of discussing the conceptions of EE as a tool to raise awareness for a transformative EE. According to the evaluation of the referees, the proposed Project in ABP and other elements inserted in the product proved to be valid and appropriate for the approach of environmental issues.